Dreamland : a novel - Sparks, Nicholas (New York : Random House Large Print, 2022)
When Colby Mills sees his dreams of a music career derailed by tragedy, he becomes the head of a small family farm in North Carolina. There he finds a new love interest, Morgan Lee, an aspiring musician who hopes to someday move to Nashville and become a star. Romantically, she and Colby complete each other in a way that neither has ever known. Hundreds of miles away, Beverly is fleeing an abusive husband with her six-year-old son. They will be drawn together in a web of life-altering connections.
Keywords: Farmers -- North Carolina -- Fiction; Man-woman relationships -- Fiction; Musicians -- Fiction; Abused women -- Fiction; Runaway wives -- Fiction; Large type books; North Carolina -- Fiction; Large type books; Romance fiction; Large type books; Romance fiction; Novels